2023
DOI: 10.3390/math11051144
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Modelling the Concentration of Vehicle-Related PM2.5 and PM10 Emissions Based on Neural Networks

Abstract: The urban environment near the road infrastructure is particularly affected by traffic emissions. This problem is exacerbated at road junctions. The roadside concentration of particulate (PM2.5 and PM10) emissions depends on traffic parameters, meteorological conditions, the characteristics and condition of the road surface, and urban development, which affects air flow and turbulence. Continuous changes in the structure and conditions of the traffic flow directly affect the concentration of roadside emissions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Then, we should analyze the impact on these characteristics of vehicles belonging to other groups: group 3 (TV-3) (trucks weighing from 3.5 to 12 tons); 4 (TV-4) (trucks weighing over 12 tons) and 5 (TV-5) (buses weighing over 3.5 tons). Notably, this study does not consider group 2 (TV-2) vehicles (vans and minibuses weighing up to 3.5 tons), since previous study [43] have shown that they do not significantly change the temporal characteristics of the flow of vehicles belonging to the first group.…”
Section: Analysis Of the Vehicle Queue Structurementioning
confidence: 99%
“…Then, we should analyze the impact on these characteristics of vehicles belonging to other groups: group 3 (TV-3) (trucks weighing from 3.5 to 12 tons); 4 (TV-4) (trucks weighing over 12 tons) and 5 (TV-5) (buses weighing over 3.5 tons). Notably, this study does not consider group 2 (TV-2) vehicles (vans and minibuses weighing up to 3.5 tons), since previous study [43] have shown that they do not significantly change the temporal characteristics of the flow of vehicles belonging to the first group.…”
Section: Analysis Of the Vehicle Queue Structurementioning
confidence: 99%
“…Hybrid recommender systems integrate both contentbased and collaborative approaches, synergistically optimizing performance and honing the precision of recommendations. The amalgamation of these techniques empowers recommender systems to furnish users with suggestions that are not only personalized but also highly accurate [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution, specifically the presence of particulate matter with a diameter of 10 µm or less (PM10), poses a significant threat to public health and the environment [1]. PM10 particles are small enough to be inhaled deep into the lungs, leading to a range of health problems [2].…”
Section: Introductionmentioning
confidence: 99%